Measurement and modeling of Ar∕H2∕CH4 arc jet discharge chemical vapor deposition reactors. I. Intercomparison of derived spatial variations of H atom, C2, and CH radical densities - Rennick, C. J.; Ma, J.; Henney, J. J.; Wills, J. B.; Ashfold, M. N. R.; Orr-Ewing, A. J.; Mankelevich, Yu. A. (Journal of applied physics, 2007)
Comparisons are drawn between spatially resolved absorption spectroscopy data obtained for a 6.4kW dc arc jet reactor, operating with Ar∕H2∕CH4 gas mixtures, used for deposition of thin, polycrystalline diamond films, and the results of a two-dimensional (r,z) computer model incorporating gas activation, expansion into the low pressure reactor, and the chemistry of the neutral and charged species. The experimental measurements, using either cavity ring-down spectroscopy or diode laser absorption spectroscopy, determined absolute number densities of H(n=2) atoms, and column densities of C2(aΠu3), C2(XΣg+1), and CH(XΠ2) radicals, with vibrational and rotational quantum state resolutions, and their variation with height through the horizontally propagating arc jet plume. Spectra were also analyzed to obtain temperatures and local electron densities [from Stark broadening of H(n=2) absorption lines]. The experimental data are directly compared with the output data of the model that returns spatially inhomogeneous temperature, flow velocities, and number densities of 25 neutral and 14 charged species. Under the base operating conditions of the reactor [11.4SLM (standard liters per minute) of Ar and 1.8SLM of H2 entering the primary torch, with addition of 80SCCM (SCCM denotes cubic centimeter per minute at STP) of CH4 downstream; 6.4kW input power; reactor pressure of 50Torr], the calculated and measured column and number densities agree to within factors of 2–3, the model reproduces the spatial dependence of column densities, and the mean temperatures of C2(a) and CH(X) radicals derived from spectra and model results are in good agreement. The model also captures the variation of these parameters with changes to operating conditions of the reactor such as flows of H2 and CH4, and input power. Further details of the model and the insights it provides are the subject of the accompanying paper [Mankelevich et al., J. Appl. Phys. 102, 063310 (2007) ].